2020
DOI: 10.1080/23311975.2020.1780101
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate tax avoidance explain firm performance? Evidence from an emerging economy

Abstract: Corporate tax avoidance is an act aiming at reducing tax amount liable to the government, which is expected to raise firm value. However, agency theory postulates that opportunistic managers can lower tax liabilities through the arrangement of complex transactions, enabling them to shirk or pursue own interests. Therefore, the need to examine the link between corporate tax avoidance and firm performance is evident, yet there has not been any research on this in the context of Vietnam, a country plagued with ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 52 publications
7
28
1
7
Order By: Relevance
“…Currently, both exchanges have around 735 firms listed, although there are a few new ones. Financial, insurance, and investment firms are always treated as independent study samples due to their distinct business features [74]. Following the removal of the aforementioned samples, the author then eliminates firms from the final sample that have incomplete data or are missing too much.…”
Section: Data Collectionmentioning
confidence: 99%
“…Currently, both exchanges have around 735 firms listed, although there are a few new ones. Financial, insurance, and investment firms are always treated as independent study samples due to their distinct business features [74]. Following the removal of the aforementioned samples, the author then eliminates firms from the final sample that have incomplete data or are missing too much.…”
Section: Data Collectionmentioning
confidence: 99%
“…They described CTA as "all transactions that can affect a firm's explicit tax liability". Literature studies have revealed that CTA has an association with firm value and various authors examined this association in different contexts (Desai & Dharmapala, 2009;Chen et al, 2014;Dyreng et al, 2016;Zhang et al, 2017;Khuong et al, 2020;Minh Ha et al, 2021;Hasan et al,2021).…”
Section: Corporate Tax Avoidancementioning
confidence: 99%
“…Hasan et al (2021) also found a positive relationship between CTA and FV in high OC firms. In contrast, extensive empirical evidence has been accumulated in the literature to support the notion that CTA has a negative impact on company performance (Khuong et al, 2020). Some of the basic reasons for this negative relationship include non-financial costs attached with CTA activities like reputation cost, managerial rent extraction, and information asymmetry Cook et al, 2017).…”
Section: Previous Studies On Corporate Tax Avoidance and Firm Valuementioning
confidence: 99%
See 2 more Smart Citations